Pandangan MUI Kota Medan tentang Pemberian Masjid sebagai Mahar Pernikahan - Marpaung, Ichlasul Amarul Haq; Lubis, Azwani (AL-SULTHANIYAH, 2025)
Recently, a phenomenon has emerged involving the use of a mosque as a marriage dowry (mahar), which has sparked legal debates. This study aims to analyze the perspective of the Indonesian Ulema Council (Majelis Ulama Indonesia or MUI) of Medan City regarding the practice of giving a mosque as a mahar in marriage. The research employs a descriptive qualitative method with a normative and conceptual legal approach. Data were collected through interviews with representatives of MUI Medan and a literature review of Islamic legal texts and scholarly articles related to marriage and waqf. The findings indicate that MUI Medan rejects the validity of using a mosque as mahar because a mosque is considered waqf property, which has been removed from private ownership and therefore does not meet the Islamic legal requirements for a valid mahar—that it must be something that can be lawfully owned and transferred. Nevertheless, the marriage contract remains valid if all its pillars and conditions are fulfilled, but the invalid mahar must be replaced with a mahar mithil (a customary or appropriate dowry). This study recommends the issuance of an official and explicit fatwa by the MUI to prevent public misunderstanding and to serve as guidance for marriage officers and related parties in the practice of marriage.